Drug profile: transdermal rivastigmine patch in the treatment of Alzheimer disease - Emre, Murat; Bernabei, Roberto; Blesa, Rafael; Bullock, Roger; Cunha, Luis; Daniëls, Hugo; Dziadulewicz, Edward; Förstl, Hans; Frölich, Lutz; Gabryelewicz, Tomasz; Levin, Oleg; Lindesay, James; et al. (CNS neuroscience & therapeutics, 2010)
Cholinesterase inhibitors constitute one of the mainstays of treatment of Alzheimer disease (AD). Gastrointestinal side effects, difficulty accessing therapeutic doses and poor patient compliance have been identified as barriers to effective treatment with these substances. The rivastigmine transdermal patch provides continuous delivery of drug through the skin into the bloodstream, avoiding the fluctuations in plasma concentration associated with oral administration. This pharmacokinetic profile is associated with reduced side effects, resulting in easier access to expected target doses. These benefits, along with other practical advantages of the transdermal patch, may contribute to enhanced patient compliance. Here, we present a review of the current literature on rivastigmine patch, and offer advice based on our own collective clinical experience. Rivastigmine patch provides an efficient option for managing patients with AD, to be considered among the first line therapies for the disease.
Gesehen am 22.05.2023